IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI TERINTEGRASI PEMBELAJARAN SOSIAL DAN EMOSIONAL UNTUK MEWUJUDKAN PROFIL PELAJAR PANCASILA - Ana Ana (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
The students we have in class are of course very diverse. So that differentiated learning that is integrated with social and emotional learning is needed. However, the learning carried out by this writer has not been able to accommodate the learning needs of various students so that the learning atmosphere is not conducive and the learning objectives, namely realizing the Pancasila student profile, have not been realized. Departing from this, the author implements differentiated learning that integrates social and emotional learning for students in class VI Theme 1 Sub Theme 1 Learning 2, with the hope that learning is more conducive and able to realize the profile of Pancasila students. The results of the learning activities turned out to be very good, namely learning was more conducive and the creativity of students also increased. The practice of differentiated learning that integrates social and emotional learning which works well, the authors conclude as a best practice (good practice) that is able to realize the Pancasila Student Profile.